توظيف مقاصد القرآن في قصة ضيف إبراهيم ودواعيه في إقامة الدعوة الاسلامية دراسة تحليلية - Fatmah Taufik Hidayat; Laila Sari Masyhur (Raudhatun Najah Publisher, 2023)
Honouring guests is an Islamic religious doctrine and a concern and humanity that is a parameter of the quality of one's faith. So far, the study that discusses visiting from the perspective of the Qur'an has only answered part of the problem regarding the manners and ethics of honoring guests, while the discussion of a verse can be explored for the purposes and objectives behind it, including knowing the values of Islamic values that uphold the morality and behaviour of a Muslim in the Qur'an. This study uses a type of library research with the method of maqasidi interpretation approach to describe the maqasid al-Qur'an initiated by Wshfi Asyur with the aim of examining the intention behind the verse. The conclusions that can be drawn from this study are; first, that the maqasidi interpretation of the verse glorifying a guest in the story of dhayif Ibrahim proves one of the aspects and essence of Islam as a whole, because the behaviour of glorifying guests is oriented towards solving the problems of people, not only for Muslims but for humanity as a whole. Secondly, this study emphasises that an in-depth, balanced and comprehensive reading makes the interpretation of the verse glorifying guests capable of presenting Islam as it is as a whole. And create a unity of concern